5y+3=7(y-1)

Simple and best practice solution for 5y+3=7(y-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y+3=7(y-1) equation:



5y+3=7(y-1)
We move all terms to the left:
5y+3-(7(y-1))=0
We calculate terms in parentheses: -(7(y-1)), so:
7(y-1)
We multiply parentheses
7y-7
Back to the equation:
-(7y-7)
We get rid of parentheses
5y-7y+7+3=0
We add all the numbers together, and all the variables
-2y+10=0
We move all terms containing y to the left, all other terms to the right
-2y=-10
y=-10/-2
y=+5

See similar equations:

| -3p-13+10p=2+2p | | 11=-v+290 | | 3(5+x)+60=180 | | 5(u-3)=7u-7 | | -15=3-6v | | 9=8c+15c/c | | 4(3x+2)=6(2x+1) | | 29-6x=-65 | | 10(2x-5)=2x+2(x+1) | | 32x=20(x+18) | | -3x+18=(13-10+4x-2) | | 11+13(x-2)=15x-2(x+4) | | x+(5/6x)=33 | | 21/2x=63 | | 101/2x=63 | | 7.4b=5 | | 2x^2+50=-116 | | 6x-4x=2x+6 | | 2z^2+50=~166 | | Y=-50+b | | -4|3x-5|=8 | | 6(0)-8y=-24 | | X-(x*0.05)=15634 | | −2(−x+4)+4x−3=−2(−x+4)+4x−3=  3131 | | (6+x)/2=x+4 | | 3/2t2=4 | | 2x+3(2x-5)+4=x+3(3x-2)-6 | | x2−19x+102=−x-6 | | (1/16)=8^(4x-2) | | 7x+40=(1+4x) | | 4*4*4*4*3*4*4*4*4*7*4*4*4*4*29*4*4*4*4*59=x | | 58x=765 |

Equations solver categories